The molecular mechanism of the control of excitation energy dissipation in chloroplast membranes. Inhibition of delta pH-dependent quenching of chlorophyll fluorescence by dicyclohexylcarbodiimide. - Ruban, A; Walters, R; Horton, P (1992)
Non-radiative dissipation of absorbed excitation energy in chloroplast membranes is induced in the presence of the trans-thylakoid proton motive force; this dissipation is measured as high energy state quenching of chlorophyll fluorescence, qE. It has been suggested that this results from a low pH-induced structural alteration in the light harvesting complex of photosystem II, LHCII [(1991) FEBS Letters 292, 1-4]. The effect of the carboxyl-modifying agent, dicyclohexylcarbodiimide (DCCD), on energy dissipation in chloroplast membranes has been investigated. At concentrations below that required to inhibit electron transport, DCCD caused a decrease in the steady state delta pH, completely inhibited qE and also inhibited the low pH-dependent induction of qE. DCCD binding to polypeptides in the 22-28 kDa range correlated with inhibition of qE. It is suggested that DCCD reacts with amino acid residues in LHCII whose protonation is the primary event in the induction of energy dissipation. This LHCII domain may be identical to one forming a proton channel linking the site of PSII-dependent water oxidation to the thylakoid lumen [(1990) Eur. J. Biochem. 193, 731-736].